Lath hammer - Skinner, Perle Harrison (My University, 1907)
Introduction: A trite proverb, and one quite frequently quoted in modern mechanical literature, is, "By the hammer and hand all the arts do stand.” These few words sum up a great deal of information concerning elementary mechanics. If we examine some of the more elaborate arts of modern times, or give our attention to pursuits in which complicated mechanism is employed, we may at first be impressed that however correct this expression may have been at one time, it is not applicable at the present day. But if we pursue our investigation far enough, and trace the progress of the industry, whatever its nature, back to its origin, we find sooner or later that both hammer and hand have everything to do with its establishment and maintenance. Take, as an example, textile fabrics. They are products of looms. In the construction of the looms, the hammer was used to a great extent; but back of them were other machines of varying degrees of excellence, in which the hammer played a still more important part, until finally we reach a point where the hand and hammer laid the very foundation of the industry. Even at the present time it would be necessary to go back to this same point if, by some unaccountable means, our present equipment of modern machinery should be blotted out of existence. This is the rule with no exceptions
Citation: Skinner, Perle Harrison. Lath hammer. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Lath Hammer; Hammer Versus Hand; Mechanical Tools; Theses